Novel Mycoplasma bovis membrane lipoproteins induce the inflammatory response of host epithelial cells and macrophage - Yuan, Xiaotan; Ma, Jiating; Wu, Yiming; Zhao, Gang; Wang, Yujiong (Frontiers in Immunology, 2025)
BackgroundMycoplasmopsis bovis, caused by Mycoplasma bovis infection, can lead to severe pneumonia and mastitis in cattle, resulting to significant economic losses to the global cattle industry. The membrane lipoprotein of M. bovis is recognized as a critical virulence factor, playing a key role in pathogenesis and modulating host cell immune responses. Therefore, identifying M. bovis membrane lipoproteins is of great significance to explore their roles in regulating the immune response of host cells.MethodsIn this study, 10 immunogenic M. bovis membrane lipoproteins were predicted by bioinformatics software, with 8 of them subsequently expressed and purified. Four lipoproteins, namely MbovP0659, MbovP0536, MbovP0393 and MbovP0585 were then shown to react with M. bovis-infected cattle serum, hence demonstrated their significantly stronger immunogenicity compared with others. Furthermore, polyclonal antibodies against the eight membrane lipoproteins were prepared and used to detect their subcellular localization.ResultsThe results revealed that MbovP0592 was a secreted lipoprotein, while MbovP0659, MbovP0536, MbovP0393 and MbovP0585 were confirmed as membrane lipoproteins. Finally, the effects of MbovP0592, MbovP0659, MbovP0536, MbovP0393 and MbovP0585 on the inflammatory cytokines of host epithelial cells and macrophages were characterized by qRT-PCR.ConclusionThis study identified a secretory lipoprotein MbovP0592 along with four immunogenic membrane lipoproteins, all of which possess the ability to initiate inflammatory responses in host cells. These results provide potential candidates for developing subunit vaccines and study the pathogenic mechanism of M. bovis.